2018
DOI: 10.1186/s12890-018-0753-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of asthma and associated factors in an urban Pakistani population: adult asthma study-Karachi

Abstract: BackgroundThis study was conducted in order to determine the prevalence of asthma and associated risk factors in the adult population of Karachi, Pakistan.MethodsThis multi-stage, cross-sectional survey was conducted from May 2014–August 2015; comprising 1629 adults in 75 randomly selected clusters in Karachi, Pakistan. Definitions included: ‘self-reported asthma’, ‘reversibility in FEV1’ and ‘respiratory symptoms and reversibility in FEV1’.ResultsPrevalence of asthma was 1.8% (self-reported) (95% CI: 1.0–2.6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 33 publications
0
44
1
Order By: Relevance
“…5 Razzaq S et al, found that the risk of exacerbations of bronchial asthma was 1.9 times more among those aged >38 years of age. 6 Kang HR et al, also observed similar finding that exacerbations of bronchial asthma episodes were significantly more among those aged more than 45 years. 7 Smith K et al, also noted in their study that elderly were at more risk of exacerbations of bronchial asthma.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…5 Razzaq S et al, found that the risk of exacerbations of bronchial asthma was 1.9 times more among those aged >38 years of age. 6 Kang HR et al, also observed similar finding that exacerbations of bronchial asthma episodes were significantly more among those aged more than 45 years. 7 Smith K et al, also noted in their study that elderly were at more risk of exacerbations of bronchial asthma.…”
Section: Discussionmentioning
confidence: 62%
“…10 Razzaq S et al, this risk was 1.9 times more among those with history of allergies. 6 Anto JM et al, this risk was 1.98 times more among those having nasal allergy. 11 But we did not find this association as significant.…”
Section: Discussionmentioning
confidence: 91%
“…It is estimated an increment of 33% or 400 million people will be affected by 2025 [4]. In Pakistan, according to a report on the global burden of asthma, the prevalence is 4.3% and in rural areas, it is quite high [5]. Asthma's risk factors include inhaling asthma "triggers", for example, allergens, physiological conditions, tobacco smoke, and certain medications [6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other chronic diseases, asthma has a relatively low fatality rate therefore asthma has become an economic burden that influences the quality of life of the patients [5][6][7]. It is essential to understand the cost of asthma per episode of exacerbation to effectively use the current asthma medication resources, and to identify where the burden occurs and learn to achieve optimal cost-effectiveness [4][5][6][7]. The economic evaluation of a disease can lay the basis for precise healthcare decisions that can influence financial resources more effectively toward the management of that disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that high-income countries of the world have more people suffering from asthma than in average or low-income countries [3]. The report on global burden of asthma estimated the prevalence of asthma in Pakistan to be 4.3% [4]. Despite being quite common, it is not adequately being managed, leading to low Quality of Life (QOL) and early death.…”
Section: Introductionmentioning
confidence: 99%